K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

9 tháng 10 2021

\(\left(4x-1\right)^2-4x^2\)

\(=\left(4x-1\right)^2-\left(2x\right)^2\)

\(=\left(4x-1-2x\right)\left(4x-1+2x\right)\)

\(=\left(2x-1\right)\left(6x-1\right)\)

10 tháng 10 2021

`(4x-1)^2-4x^2=(4x-1)^2-(2x)^2=(4x-1-2x)(4x-1+2x)=(2x-1)(6x-1)`

11 tháng 8 2023

\(4x^2-4x+1=\left(2x\right)^2-2.2x.1+1^2=\left(2x-1\right)^2\\ ---\\ 4x^2-4x-3\\ =4x^2-4x+1-4\\ =\left(2x-1\right)^2-2^2=\left(2x-1-2\right)\left(2x-1+2\right)\\ =\left(2x-3\right)\left(2x+1\right)\)

1: =(2x)^2-2*2x*1+1^2

=(2x-1)^2

2: =4x^2-6x+2x-3

=2x(2x-3)+(2x-3)

=(2x-3)(2x+1)

19 tháng 10 2023

\(4x^4+4x^3+5x^2+2x+1\)

\(=4x^4+2x^3+2x^2+2x^3+x^2+2x^2+x+1\)

\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)

\(=\left(2x^2+x+1\right)\left(2x^2+x+1\right)\)

\(=\left(2x^2+x+1\right)^2\)

23 tháng 7 2015

 = ( x - y)^2 - z^2 

= ( x - y -z)(x - y + z) 

5 tháng 12 2016

= (4x2 + 4x+ 1) - y2

=(4x2 + 4x +1) -y2

=[(2x) + 2.2x.1 +1] - y2

=(2x +1)2 - y2

=[(2x +1) -y].[(2x +1) +y]

=(2x +1 -y).(2x +1 +y)

20 tháng 8 2017

 4x^2 - y^2 + 4x + 1 

=4x2+4x+1-y2

=((2x)2+2.2x.1+1)-y2

= (2x+1)-y2

=(2x+1+y)(2x+1-y)

7 tháng 11 2015

C1:        \(4x^2-4x+1=\left(2x-1\right)^2\)       (Hằng đẳng thức bạn ạ)

C2:        \(4x^2-4x+1\)

           =\(4x^2-2x-2x+1\)

            =\(2x\left(2x-1\right)-\left(2x-1\right)\) 

             =\(\left(2x-1\right)\left(2x-1\right)\)

               =\(\left(2x-1\right)^2\) 

Mình chắc 100% đó .     **** mình bạn na !!!

19 tháng 10 2016

\(x^3+4x^2+4x+1\)

\(=x^3+3x^2+x+x^2+3x+1\)

\(=x\left(x^2+3x+1\right)+\left(x^2+3x+1\right)\)

\(=\left(x+1\right)\left(x^2+3x+1\right)\)

6 tháng 8 2015

(4x2+4x+1)-y2

=(2x+1)2-y2

=(2x+1+y)(2x+1-y)

6 tháng 8 2015

= ( 4x^2 + 4x + 1 ) - y^2

= ( 2x +  1 )^2  - y^2 

= ( 2x + 1 - y)( 2x + 1 + y) 

4 tháng 9 2018

1) ( 4x + 1 )2 + ( 4x - 1 )2 - 2( 4x + 1 ).( 4x - 1 )

= ( 4x + 1 - 4x - 1 )2

= 22

= 4

2) 4x2 - 9 + ( 2x + 3 )

= ( 2x )2 - 32 + ( 2x + 3 )

= ( 2x + 3 ).( 2x - 3 ) + ( 2x + 3 )

= ( 2x + 3 ). ( 2x - 3 + 1 )

= ( 2x + 3 ) .( 2x - 2 )

= 2.( 2x + 3 ) .( x - 1 )

24 tháng 9 2018

1, (4x+1)^2 + (4x-1)^2 - 2(4x+1)(4x-1)

=[(4x+1)-(4x-1)]^2

=(4x+1-4x+1)^2

=2^2

=4

2, 4x^2 - 9 +(2x+3)

=(4x^2 - 9)+(2x+3)

=(2x+3)(2x-3)+(2x+3)

=(2x+3)(2x-3+1)

=(2x+3)(2x-2)

=2(x-1)(2x+3)

=.= hok tốt!!